2006
DOI: 10.1080/10826080601006490
|View full text |Cite
|
Sign up to set email alerts
|

Buddhism and Adolescent Alcohol Use in Thailand

Abstract: A sample of 2019 Thai secondary school students in grades equivalent to U.S. 10 through 12 completed a 43-item alcohol expectancy questionnaire in June 2000. Factor analysis revealed four factors: (a) positive expectancies, (b) negative expectancies, (c) sex and power expectancies, and (d) religious expectancies. Practicing Buddhists were less likely to drink than nonpracticing Buddhists and had fewer positive and more negative expectancies about alcohol. Among students who did drink, Buddhist beliefs did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Positive expectancy reflects more favorable beliefs regarding the consequences of consuming alcohol (e.g., “drinking helps me feel whatever way I want to feel”), and is hypothesized to be a motivating factor for consumption (Jones et al, 2001). We also found that higher positive expectancy was related to harmful drinking across the sample, which is consistent with the limited literature on alcohol expectancy and drinking among high school students in Thailand (Newman et al, 2005, 2006). In addition to reporting higher alcohol expectancy scores, lesbian/bisexuals were simultaneously more likely to report harmful drinking.…”
Section: Discussionsupporting
confidence: 91%
“…Positive expectancy reflects more favorable beliefs regarding the consequences of consuming alcohol (e.g., “drinking helps me feel whatever way I want to feel”), and is hypothesized to be a motivating factor for consumption (Jones et al, 2001). We also found that higher positive expectancy was related to harmful drinking across the sample, which is consistent with the limited literature on alcohol expectancy and drinking among high school students in Thailand (Newman et al, 2005, 2006). In addition to reporting higher alcohol expectancy scores, lesbian/bisexuals were simultaneously more likely to report harmful drinking.…”
Section: Discussionsupporting
confidence: 91%
“…Silas Ha, the five Buddhist precepts that lay Buddhists are expected to practice (avoid killing, theft, sexual misconduct, lying, and intoxication) have been taught as a moral code of conduct (Assanangkornchai, Conigrave, & Saunders, 2002;Newman, Shell, Li, & Innadda, 2006;Sivaraksa, 1998). All participants admitted that Thai adolescents frequently ignore the practice of Silas Ha, especially concerning alcohol consumption, false speech, and preserving life (i.e., bugs, small animals).…”
Section: Downloaded By [New York University] At 23:18 30 May 2015mentioning
confidence: 94%
“…All participants admitted that Thai adolescents frequently ignore the practice of Silas Ha, especially concerning alcohol consumption, false speech, and preserving life (i.e., bugs, small animals). Researchers have documented negative associations between the fifth percept of Buddhist teachings (i.e., avoiding intoxication) and alcohol use by Thai adolescents and men (Assanangkornchai et al, 2002;Newman et al, 2006). While this study did not indicate significant associations between the concept of Silas Ha and dating violence, the failure to practice Silas Ha, especially sexual misconduct and Downloaded by [New York University] at 23:18 30 May 2015 lying, was viewed by participants as a source of tension that might lead to misunderstanding or violence between partners.…”
Section: Downloaded By [New York University] At 23:18 30 May 2015mentioning
confidence: 99%
“…In one study, Buddhist principles were used as an intervention to improve emotional intelligence for Thai youth (Sucaromana, et al, 2004). A more recent study found that both Buddhist practices and beliefs were negatively related to alcohol use among Thai adolescents (Newman, et al, 2006). Assanangkomchai and colleagues (2002) reported similar findings in a study among men that looked at their religious experiences as youths (e.g., being a temple boy, being ordained as a monk, and/or the undertaking of Buddhist study).…”
Section: Spirituality In Buddhist Societymentioning
confidence: 99%